2016
DOI: 10.1021/acs.inorgchem.5b02711
|View full text |Cite|
|
Sign up to set email alerts
|

Direct Measure of Metal–Ligand Bonding Replacing the Tolman Electronic Parameter

Abstract: The Tolman electronic parameter (TEP) derived from the A 1symmetrical CO stretching frequency of nickel-tricarbonyl complexes L− Ni(CO) 3 with varying ligands L is misleading as (i) it is not based on a mode decoupled CO stretching frequency and (ii) a generally applicable and quantitatively correct or at least qualitatively reasonable relationship between the TEP and the metal−ligand bond strength does not exist. This is shown for a set of 181 nickel-tricarbonyl complexes using both experimental and calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 120 publications
1
70
0
1
Order By: Relevance
“…[28] The electronic effect of the isothiourea ligands was assessed using the To lman electronic parameter (TEP). [29] To determine this parameter,t he synthesis of iridium(I)-isothiourea carbonyl complexes was undertaken.T he reaction of [IrCl(cod)] 2 25 with either (2S,3R)-HyperBTM (2S,3R)-3 or DHPB 1 gave monocoordinated [IrCl{(2S,3R)-HyperBTM}(cod)] (2S,3R)-26 and [IrCl(DHPB)(cod)] 27 as yellow solids in good to excellent yield. [30] In contrast, the reactiono f[ IrCl(cod)] 2 (cod)] 2 25 and free ligand in the presence of the isothiourea catalystw as attempted, only minimal product formation was achieved.…”
Section: Steric and Electronic Properties Of Isothiourea Ligandsmentioning
confidence: 99%
“…[28] The electronic effect of the isothiourea ligands was assessed using the To lman electronic parameter (TEP). [29] To determine this parameter,t he synthesis of iridium(I)-isothiourea carbonyl complexes was undertaken.T he reaction of [IrCl(cod)] 2 25 with either (2S,3R)-HyperBTM (2S,3R)-3 or DHPB 1 gave monocoordinated [IrCl{(2S,3R)-HyperBTM}(cod)] (2S,3R)-26 and [IrCl(DHPB)(cod)] 27 as yellow solids in good to excellent yield. [30] In contrast, the reactiono f[ IrCl(cod)] 2 (cod)] 2 25 and free ligand in the presence of the isothiourea catalystw as attempted, only minimal product formation was achieved.…”
Section: Steric and Electronic Properties Of Isothiourea Ligandsmentioning
confidence: 99%
“…In the case of the Tolman parameter, not only the electronic properties of the carbene influence the CO stretching modes, but also steric effects and the coupling of stretching modes. The latter two drawbacks have recently been overcome by calculating the metal–ligand electronic parameter (MLEP) [36]. Separating the influence of the σ-donor and π-acceptor abilities was limited to determining the overall donor character and taking into account the σ-donor character.…”
Section: Introductionmentioning
confidence: 99%
“…(4)The local mode analysis revealed that the Tolman electronic parameter (TEP) commonly used to indirectly characterize the metal‐ligand bond does not generally correlate with the intrinsic strength of the metal‐ligand bond as assumed so far. A new electronic parameter was introduced that is directly based on the metal‐ligand local stretching force constant, the metal‐ligand electronic parameter (MLEP), and successfully tested for 181 nickel complexes . This discovery will open new avenues for catalyst design.…”
Section: Local Vibrational Modesmentioning
confidence: 99%